Peningkatan Daya Tarik Destinasi Wisata Kalimasada melalui Sarana Edukasi Flora dan Fauna - Yulia Budiwati; Danar Kristiana Dewi; Cicilia Clara Devi Anggraini; Ratih Paramitasari; Fadloli Fadloli; Djoko Sri Bimo (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Tourism destinations are an important source of Regional Original Revenue (PAD), and Kalimasada Tourism Village is one of the local attractions with significant potential. Although it was a popular destination around 2022, visitor numbers have declined in recent years. To support its revitalization, the Community Service Team of Universitas Terbuka Surakarta developed several educational facilities based on a flora-and-fauna concept. The program included the construction of animal enclosures and a flora garden, as well as the improvement of the playground and other supporting facilities. The implementation consisted of a field needs assessment, coordination with the Village-Owned Enterprise (BUMDES), project execution, monitoring and evaluation, and follow-up planning. The results demonstrated improved readiness of the BUMDES to manage and reopen the Kalimasada tourism destination through enhanced educational attractions and upgraded infrastructure. The local community responded positively by actively participating throughout the implementation and launching activities. Both the BUMDES management and residents expressed their expectation that continuous village funding would support further tourism development, increase visitor numbers, and promote sustainable local economic growth.